The problem of off label drug use in pediatrics: pediatricians and parents survey results - E. A. Mardganieva; V. A. Ryabchenko; E. V. Malysheva; E. A. Fetisova; A. K. Krivogubets; R. E. Abishev; K. . Ramanathan (Izdatelstvo OKI, 2018)
LLC Novartis Pharma, Moscow, Russian Federation Abstract. The problem of off-label use is still unsolved during the pharmacotherapy in children. In connection with the above, the need to stimulate the conduct of specially organized clinical studies, the purpose of which will be to evaluate the efficacy and safety of using drugs in children in different age groups, becomes evident. However the complexity of the organization of clinical studies in pediatrics is associated not only with regulatory aspects but also with lack of understanding of the importance of these studies by pediatricians and parents. The authors conducted a study aimed at finding out the frequency of off-label prescriptions in the Russian Federation in pediatric practice and doctors' and parents' attitude to this kind of use of medications. The study has shown the evidence that the off-label prescription practice is widely-used in healthcare in Russia and is routine for most respondents. The highest frequency of off-label prescriptions is observed in the group of children from 0 to 5 years. The majority of physicians and parents don't consider themselves responsible for popularization of clinical trials which indicates that this problem should be widely discussed in the society. Parents trust physicians in terms of therapy choices or their recommendations regarding participation in clinical trials. A portrait of a typical "staunch opponent" of clinical trials among parents.